Integrative Taxonomy of Dermacentor variabilis (Ixodida: Ixodidae) with Description of a New Species, Dermacentor similis n. sp. Issue 6 (11th August 2021) - Lado, Paula; Glon, Mael G; Klompen, Hans
Abstract: Dermacentor variabilis is the most widely distributed three-host tick in North America, and transmits a variety of pathogens. Within the United States, this species has a discontinuous distribution, widespread east of the Rocky Mountains and with a few populations west of the Rockies. Phylogenetic evidence based on individual markers or relatively small data sets has suggested that populations at both sides of this geographic barrier may correspond to two different species. In this study, we further explore this hypothesis using an integrative taxonomy framework. Both molecular (mitochondrial and nuclear markers) and morphological analyses of specimens collected from central-eastern and western states were performed to explore species delimitation in this taxon. Results from these analyses were consistent, and provide strong evidence that D. variabilis actually corresponds to two species. Herein, the western populations are described as a new species, Dermacentor similis n. sp. The usefulness of integrative taxonomy in the context of species delimitation is also discussed.